Acute kidney: improving the pathway of care for patients and across healthcare. Issue 6 (November 2015) - Unknown
Abstract : Purpose of review: Acute kidney injury (AKI) is common, harmful and of global concern. There is a need to understand the pathway of the management of AKI in order to identify potential areas where care can be improved, for the individual and for healthcare systems. Recent findings: There has been considerable focus on risk assessment and earlier detection using changes in serum creatinine. There is less understanding of optimal management, enhanced and long-term recovery, and education to support better care. Using Kidney Disease Improving Global Outcomes-based criteria to improve the detection of AKI improves its detection, but requires supportive training and education to deliver better outcomes. Policy makers need to understand the personal and economic burden that results from AKI. There is a need to provide commissioning support, improvement methodologies, and registry initiatives with research investment to sustain progress in overall management. Summary: There is clear evidence of harm related to AKI and a need to improve the reliability of care. The prevalence is high, with the potential to significantly improve short-term and long-term care by addressing all the elements in the pathway, at both patient and system level, assessing risk, detection, treatment, and recovery.